The diagnostic accuracy of Neuropad® for assessing large and small fibre diabetic neuropathy. Issue 12 (14th July 2014) - Ponirakis, G.; Petropoulos, I. N.; Fadavi, H.; Alam, U.; Asghar, O.; Marshall, A.; Tavakoli, M.; Malik, R. A.
Abstract Aims Neuropad® is a simple visual indicator test, with moderate diagnostic performance for diabetic peripheral neuropathy. As it assesses sweating, which is a measure of cholinergic small nerve fibre function, we compared its diagnostic performance against established measures of both large and, more specifically, small fibre damage in patients with diabetes. Methods One hundred and twenty‐seven participants (89 without diabetic peripheral neuropathy and 38 with) aged 57 ± 9.7 years underwent assessment with Neuropad, large nerve fibre assessments: Neuropathy Disability Score, vibration perception threshold, peroneal motor nerve conduction velocity; small nerve fibre assessments: neuropathy symptoms (Diabetic Neuropathy Symptoms score) corneal nerve fibre length and warm perception threshold. Results Neuropad has a high sensitivity but moderate specificity against large fibre neuropathy assessments: Neuropathy Disability Score (> 2) 70% and 50%, vibration perception threshold (> 14 V) 83% and 53%, and peroneal motor nerve conduction velocity (< 42 m/s) 81% and 54%, respectively. However, the diagnostic accuracy of Neuropad was significantly improved against corneal nerve fibre length (< 14 mm/mm2) with a sensitivity and specificity of 83% and 80%, respectively. Furthermore, the area under the curve for corneal nerve fibre length (85%) was significantly greater than with the Neuropathy Disability Score (66%, P = 0.01) and peroneal motor nerve conduction velocity (70%, P = 0.03). For neuropathic symptoms, sensitivity was 78% and specificity was 60%. Conclusions The data show the improved diagnostic performance of Neuropad against corneal nerve fibre length. This study underlines the importance of Neuropad as a practical diagnostic test for small fibre neuropathy in patients with diabetes.